THE WORLD MAJOR SCIENTIFIC PERIODICALS TO BE USED BY RESEARCHERS OF “RENEWABLE ENERGY, LOCAL AND SECONDARY ENERGY RE-SOURCES” - V. S. Lazarev; A. V. Skalaban (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
It is known that the selection of аn acceptably representative sample of the world scientific periodicals to be used as backgrounds of a high-quality research should focus not only on specialized journals, but also on periodicals, the topics and the titles of which are formally not related to the research area. In the present study the determination of the best periodicals to be used in research on “Renewable energy, local and secondary energy resources” has been fulfilled with the aid of four varieties of citation analysis, twelve journals specialized in power production being used as the source items of citation data. The methods of the analysis were clarified and elaborated; the concept and the term “discipline receptivity factor” were proposed. The practical result is a list of 378 world periodicals, that is planned to be used in creating a comfortable scientific information environment by using the world leading databases reflecting the most valuable collection of scientific journals that are necessary for quality performance of scientific research on Priority areas of scientific-technical activity in the Republic of Belarus for 2016–2020 followed by the establishment of an operational system of electoral alert leading experts implementing the respective areas.